Investigating the Effect of Polymer Molecular Weight on Drag Reduction Performance Using Rotating Disk Apparatus (RDA) - Nurul Fatimah, Abdul Basir (2013)
The investigation of turbulent drag reduction, which is caused by the addition of a small amount of polymer or some other substances to the liquids flowing systems has been the focus of attention of many scientists for the last decades. Due to the reduction of the drag, pumping power for the pipeline will significantly reduced and thus will decrease the cost of electricity in total production cost. In this study, the effect of the presence of a drag reducing agent (DRA) and its variety of molecular weight on the torque produced in rotating disk apparatus containing water is investigated. The experimental procedure was divided into three parts; obtaining several different polymer molecular weights using ultrasonication method, testing the water using different polymer molecular weight at different polymer concentration and lastly is adding the different concentration of surfactant in the fixed concentration of water- polymer solution. Three polymer molecular weights are obtained by using ultrasonificator method with value of 11.7967 x106 g/mol, 4.830 x106 g/mol and 1.7179 x106 g/mol. A drastic reduction of drag in the turbulent flow of solutions as evaluated with torque differences in comparison to the pure solvent can be observed, even when only minute amounts of the additives are added. The percentage of drag reduction is relatively increases as we increase the polymer molecular weight and polymer concentration. A maximum drag reduction of 47.62% has been observed at polymer molecular weight of 11. 7697 x106 with polymer concentration of 200 ppm. In polymer- surfactant complex solution, 29% of drag reduction were reported with surfactant concentration of 2000ppm.